Inovasi dalam pengembangan kurikulum PAI pada madrasah untuk menghadapi era milenial - Abdallillah, Najwa Aisyah (Maliki Interdisciplinary Journal, 2024)
The Islamic Education Curriculum (PAI) in madrasahs (MI, MTs, MA) currently appears fragmented among subjects such as Quran Hadith, Fiqh, Aqidah, and Islamic Cultural History, and thus has not yet been fully integrated into substantive themes. This integration is essential for optimizing the religious practices and experiences of students, as they will feel comprehensively supported by various aspects of religious teachings in performing worship. The development of the PAI curriculum in madrasahs still faces various challenges due to the complexity of madrasah institutions, such as differences in ownership status, madrasah environments, and the quality of teachers. Madrasah teachers need to innovate the curriculum to address the advancements in information and communication technology, as well as issues emerging in the millennial era. The challenge is how PAI teachers in madrasahs implement these innovations. This research aims to understand the construction and development of the PAI curriculum in madrasahs in facing the millennial era. This research is qualitative with a literature study approach. The data obtained comes from various regulations, books, and journals. The qualitative approach is chosen to understand curriculum development innovations to improve the quality of madrasahs as schools with Islamic characteristics in the millennial era. The results of the literature study indicate that the construction of the PAI curriculum in madrasahs still emphasizes Subject Centered Design, which focuses on separate subjects. The most dominant determining factors are the quality of teachers and infrastructure. The ideal curriculum construction model lies in the essence and depth of the material, making the Collaborative Curriculum Madrasah’s an innovative choice for the PAI curriculum in madrasahs, deemed suitable for the millennial era with an integrated learning pattern from various PAI subjects in madrasahs.